Pseudo-malignant paranasal invasive aspergillosis showing bone destruction and FDG uptake on PET/CT: A case report. Issue 45 (11th November 2022) - Tsuda, Takeshi; Takeda, Kazuya; Fujii, Soichiro; Hayama, Masaki; Inohara, Hidenori
Abstract : Rationale: Aspergillosis is a rare disease that often occurs in patients with diabetes mellitus or compromised hosts. This study describes a 60-years-old woman with unusual pseudo-malignant paranasal invasive aspergillosis with 18 F-fluorodeoxyglucose ( 18 F-FDG) uptake treated by endoscopic sinus surgery. To the best of our knowledge, there are few reported cases of paranasal fungal infection with 18F-FDG uptake. Patients concerns: A 60-years-old woman was presented with headache and nasal obstruction. Diagnoses: Computed tomography (CT) showed a shadow with bone destruction in the sinus cavity and accumulation of 18 F-FDG uptake. The patient was diagnosed with a malignant tumor or pseudo-malignant paranasal invasive aspergillosis. Interventions: The patient underwent endoscopic sinus surgery; no neoplastic lesions were detected in the areas with CT shadows. All the observed fungal mass reservoirs were removed. Outcomes: The patient remained hospitalized for 1 week after the surgery with no significant postoperative abnormalities. There was no recurrence of the disease for 6 months, and the patient's symptoms resolved, indicating a good course of follow-up. Lessons: Invasive aspergillosis should be considered a differential disease when positron emission tomography (PET)/CT scans show FDG uptake, CT shows bone destruction, and T2-weighted MRI scans show a low signal.